From ‘intuitive’ pragmatic interventions to a systematic approach – Using implementation science to improve childhood cancer survival in low-income settings: The CANCaRe Africa experience - Trijn Israels; Barnabas Atwiine; Caitlyn Duffy; Junious Sichali; Glenn Afungchwi; Kathy Pritchard-Jones; Deborah Nyirenda; Victor Mwapasa (Pediatric Hematology Oncology Journal, 2024)
Implementation science is a relatively young field of study and is the science of delivering evidence-based interventions into routine health care. RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) is an evaluation-type implementation science framework. CANCaRe Africa is preparing a project to assess the implementation and effectiveness of a cash incentive intervention to support families with out-of-pocket costs to prevent treatment abandonment and increase childhood cancer survival in sub-Saharan Africa. Our strategy is to enhance the dissemination of our research findings to local policymakers who can support the scale-up of evidence-based clinical interventions and locally effective implementation strategies. It can be done best by embedding implementation science into our clinical research approaches.